Kakawin Udayana: Kajian Hermeneutika atas Teks Kakawin Minor dalam Tradisi Bali - Tedjowirawan, Anung (Manuskripta, 2019)
Kakawin Udayana (Udayanacarita) is a kakawin minor in Balinese tradition. Kakawin Udayana tells the life story of King Udayana (Sri Manmatamurti, Sri Kamamurti), the son of Sang Sri Satasenya, the descendant of Pandu. Prabangkara's painting led Udayana fell in love and sought to fondle Dewi Anggarawati (Dewi Anggara, Sri Sudewi), the consort of Maharaja Candrasena from Yarwanti Kingdom. As a result, Maharaja Candrasena ordered Perwira Pemberani (The Brave Officers) to trick and arrest King Udayana. Finally, King Udayana sentenced to death. The primary source of this research is Kakawin Udayana. Sĕrat Darmasarana, Sĕrat Yudayana and Adiparwa, the first part of Mahabharata, are also used as comparison and complementary materials. This research applies the theory of hermeneutics and comparative literary theory. The method used in this research is by way of proving the researcher’s various presumptions about the character of Udayana in Kakawin Udayana. Evidently, the choosing of Udayana’s character is to represent Udayana, the king of Bali who has overthrown Erlangga (Airlangga). Thus, there is a point of association connecting Kakawin Udayana (Balinese tradition) with SĕratDarmasarana, Sĕrat Yudayana (Javanese tradition), and Adiparwa (Indian tradition). === Kakawin Udayana (Udayanacarita) adalah kakawin minor dalam tradisi Bali. Kakawin Udayana mengisahkan kisah kehidupan Raja Udayana (Sri Manmatamurti, Sri Kamamurti), putra Sang Sri Satasenya, keturunan Pandu. Melalui lukisan Prabangkara menyebabkan Udayana jatuh cinta dan berusaha mencumbui Dewi Anggarawati (Dewi Anggara, Sri Sudewi), permaisuri Maharaja Candrasena dari Kerajaan Yarwanti. Akibatnya Maharaja Candrasena memerintahkan Perwira Pemberani untuk memperdaya serta menangkap Raja Udayana. Raja Udayana akhirnya dijatuhi hukuman mati. Bahan utama penelitian ini adalah Kakawin Udayana, dan sebagai bahan pelengkap pembanding adalah Sĕrat Darmasarana, Sĕrat Yudayana maupun Adiparwa bagian pertama Mahabharata. Dalam penelitian teori yang digunakan adalah teori hermeneutika dan teori sastra bandingan. Adapun metode yang dipakai dalam penelitian ini adalah dengan jalan membuktikan dugaan peneliti atas berbagai asumsi yang muncul dalam pikiran peneliti tentang tokoh Udayana dalam Kakawin Udayana. Pemilihan tokoh Udayana ini rupanya dalam rangka merepresentasikan Udayana, Raja Bali yang menurunkan Erlangga (Airlangga). Dengan demikian ada titik kaitan antara Kakawin Udayana (tradisi Bali) dengan Sĕrat Darmasarana, Sĕrat Yudayana (tradisi Jawa) maupun Adiparwa (tradisi India).